BLOOD PRESSURE AND ARTERIAL STIFFNESS DYNAMICS DEPENDING ON THE DURATION OF CPAP NIGHT SESSIONS IN PATIENTS WITH SEVERE OBSTRUCTIVE SLEEP APNEA - M. V. Gorbunova; S. L. Babak; T. V. Adasheva; A. G. Malyavin (SINAPS LLC, 2019)
Background: Numerous studies on the pathophysiological mechanisms of obstructive sleep apnea discover the relationship between obstructive sleep apnea and cardiovascular diseases, its contribution to the development of resistant hypertension and endothelial remodeling. Continuous Positive Airway Pressure (CPAP) is the only reasonable pathogenetic therapy in these patients. This treatment regimen implies the creation of a "pneumatic stent" with a given level of positive pressure on the inhalation and exhalation of the patient, allowing to stabilize the lumen of the upper respiratory tract and prevent the pharyngeal collapse. However, the effects and the required duration of CPAP of night sessions to achieve the target values of blood pressure and restore arterial stiffness in patients with severe obstructive sleep apnea with resistant hypertension remain poorly understood. Objective: to study the dynamics of blood pressure, arterial stiffness and endothelial dysfunction in patients with severe obstructive sleep apnea with resistant hypertension, depending on the duration of auto-adjusting CPAP (A-Flex therapy). Methods: the prospective single-center study enrolled 168 patients with obstructive sleep apnea with resistant hypertension (139 males, 46,6 ± 9,0 y. o.) with apnea-hypopnea index >30 events /hour. The night polygraphy study was performed to calculate AHI, oxygen desaturation index, mean nocturnal saturation (SpO2 ) according to the requirements of American Academy of Sleep Medicine. Endothelial function of blood vessels was assessed manually to peripheral arterial tone. The reactive hyperemia index and augmentation index was calculated. Blood pressure was monitored by office measurement, daily monitoring of blood pressure, and by individual patient diaries. Optimal level of CPAP-treatment was adjusted at home. Apnea-hypopnea index, the level of air leakage, average pressure and compliance to CPAP-therapy were established in accordance with international requirements. Results: In the group of patients, treated with night sessions of A-Flex > 6 h/night, significant dynamics was observed by the 6th month of treatment. That is, a decrease in RHI by -1.33 (95% CI from -2.25 to -0.41; P = 0.002), a decrease in AI by -12.4% (95% CI from -18.42 to -6.38; P = 0.001), a decrease in mean SBP (24 h) by -33.6 mm Hg (95% CI from -44.1 to -23.2; P = 0.002) and decrease in mean DBP (24 h) by -20.2 mm Hg (95% CI from -29.4 to -11.1; P = 0.001), with a decrease in rate of morning rise of SPB by -22.4 mm Hg/h (95% CI from -24.7 to -20.1; P = 0.002) and a decrease in rate of morning rise of DPB by -17.4 mm Hg/h (95% CI from -19.5 to -15.3; P = 0.003). The best target values were achieved by the 12th month of treatment: a decrease in RHI by -2.11 (95% CI from -2.57 to -1.65; P = 0.001), a decrease in AI by -28.5% (95% CI from -37.06 to -19.94; P = 0.002), a decrease in mean SBP (24 h) by -39.7 mm Hg (95% CI from -48.9 to -30.5; P = 0.001) and decrease in mean DBP (24 h) by -26.8 mm Hg (95% CI from -36.1 to -17.5; P = 0.001), with a decrease in rate of morning rise of SPB by -22.5 mm Hg/h (95% CI from -23.6 to -21.4; P = 0.001) and a decrease in rate of morning rise of DPB by -19.4 mm Hg/h (95% CI from -20.7 to -18.1; P = 0.002). Conclusions: in patients with severe obstructive sleep apnea and resistant hypertension only CPAP-therapy in the A-Flex mode > 6 h/night allows to achieve target blood pressure, restores endothelial function and arterial stiffness, therefore reducing the risks of cardiovascular complications.